Analysis of External and Internal Factors in Tuberculosis Control Program in Sinak District, Puncak Regency, Central Papua Province - Pangemanan, Olvina Mieke Lydia; Makaba, Sarce; Tingginehe, Rosmin (Asian Journal of Healthcare Analytics, 2025)
Tuberculosis (TB) is an infectious disease that is still a public health problem in Central Papua, especially in Sinak District, Puncak Regency. This study aims to analyze the influence of internal and external factors that affect the effectiveness of TB prevention programs, and propose strategies to be implemented to improve the success of TB treatment. The research used a qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and document analysis using the SWOT method, then presented thematically. The results found that internally, limited human resources, limited facilities, and weak management systems were the main obstacles to the program. Externally, extreme and isolated geographical conditions, security disturbances from KKB, and lack of external support are the main challenges. Existing strategies have not optimally addressed the complexity of these obstacles. Therefore, increasing the quantity and quality of health workers, community-based approaches and cross-sectoral support are needed to improve the effectiveness of TB prevention programs specifically in Sinak District.